2005
DOI: 10.1002/jssc.200500097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of methoxypyrazines in wine using headspace solid phase microextraction with isotope dilution and comprehensive two‐dimensional gas chromatography

Abstract: This study reports an optimized headspace-solid phase microextraction (HS-SPME) method for the determination of methoxypyrazines in wine. Analysis was performed by using comprehensive two-dimensional gas chromatography with novel detection capabilities, including nitrogen phosphorus detection (GC x GC-NPD) and time-of-flight mass spectrometry (GC x GC-TOFMS). In the latter, stable isotope dilution was performed for the quantitation of 2-methoxy-3-(2-methylpropyl) pyrazine (IBMP), using labelled 2-(2H3)methoxy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 16 publications
2
60
0
Order By: Relevance
“…The solid-phase microextraction (SPME) method has been widely used in flavor analysis of wine (Ryan et al, 2005;Rodrigues et al, 2008;De León-Rodríguez et al, 2006). Luo et al (2008) identified a total of 97 volatile and semivolatile compounds using SPME-GC-MS; among them, 39 were volatile.…”
Section: -2008 (Shaoxing Rice Wine) Defines That Shaoxing Rice Wmentioning
confidence: 99%
“…The solid-phase microextraction (SPME) method has been widely used in flavor analysis of wine (Ryan et al, 2005;Rodrigues et al, 2008;De León-Rodríguez et al, 2006). Luo et al (2008) identified a total of 97 volatile and semivolatile compounds using SPME-GC-MS; among them, 39 were volatile.…”
Section: -2008 (Shaoxing Rice Wine) Defines That Shaoxing Rice Wmentioning
confidence: 99%
“…HS-SPME is a simple, rapid, solvent-free and low-cost sampling method for extracting volatile and semi-volatile compounds. This technique had been applied to the analysis of volatile compounds in alcoholic beverages, for example, wine 25 , Chinese liquor 7 and cider 10,29 .…”
Section: Introductionmentioning
confidence: 99%
“…In this work the two different extraction technologies for olive oil production, decanter and pressing by hydraulic press, were evaluated by means of volatile compounds analysis made by HS-SPME-GC × GC/ToF-MS using a longitudinal cryofocusing modulator system (LCMS) [40][41][42][43][44][45][46]. The aim was to verify if the differences, used to classify the olive oils studied under different groups, after submitting the individual peak area data, of each contour plot, to labourious principal component analysis, are also identified using ImageJ software and are enough to allow simple image comparisons to be made.…”
Section: Introductionmentioning
confidence: 99%